2022
DOI: 10.1542/peds.2021-052888l
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Dysfunction Criteria in Critically Ill Children: The PODIUM Consensus Conference

Abstract: CONTEXT Previous criteria for coagulation dysfunction in critically ill children were based mainly on expert opinion. OBJECTIVE To evaluate current evidence regarding coagulation tests associated with adverse outcomes in children to inform criteria for coagulation dysfunction during critical illness. DATA SOURCES Electronic searches of PubMed and Embase were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We also found that Fib was a protective factor for critical illness in children, indicating that the decreased Fib level (<1.48 g/L) was relative to the poor prognosis of critically ill children. This is consistent with a previous study for pediatric critical illness which recommended that the low level of Fib (<1.50 g/L) was linked to high mortality (29). Nonetheless, Bredbaca et al (30) reported that patients with early signs of hypercoagulation, as evaluated by elevated fibrin levels, would experience more organ failure and have higher in-hospital mortality compared to those with normal fibrin levels in ICU patients.…”
Section: Discussionsupporting
confidence: 88%
“…We also found that Fib was a protective factor for critical illness in children, indicating that the decreased Fib level (<1.48 g/L) was relative to the poor prognosis of critically ill children. This is consistent with a previous study for pediatric critical illness which recommended that the low level of Fib (<1.50 g/L) was linked to high mortality (29). Nonetheless, Bredbaca et al (30) reported that patients with early signs of hypercoagulation, as evaluated by elevated fibrin levels, would experience more organ failure and have higher in-hospital mortality compared to those with normal fibrin levels in ICU patients.…”
Section: Discussionsupporting
confidence: 88%
“…Concurrent thrombocytopenia was nearly ubiquitous among those with abnormal clotting parameters that received treatment. Coagulation dysfunction criteria in critically ill children were recently proposed following systematic review as part of the PODIUM Consensus Conference ( 30 ). Importantly, this comprehensive work was not intended for the preterm or NICU population.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible patients had a history of exposure to hot and humid weather or high-intensity activity, and they met at least one of the following criteria based on the Chinese Expert Consensus on the Diagnosis and Treatment of Heatstroke ( 1 ): (1) neurological dysfunction, including coma, convulsions, delirium, or abnormal behavior; (2) core temperature ≥ 40°C; (3) functional impairment of at least two organs; or (4) severe coagulopathy or DIC. Severe coagulopathy was defined as the presence of at least two of the following criteria: platelet count < 100,000 cells per μL, international normalized ratio > 1.5, fibrinogen level < 1.50 g/L, and D-dimer value above 10 times the upper limit of normal ( 11 ). Patients were excluded if they were younger than 18 years, if they had a congenital coagulopathy or severe chronic disease of the liver or kidney, or if they were using anticoagulant drugs at admission.…”
Section: Methodsmentioning
confidence: 99%